Sexual Harassment and Feeding Inhibition between two Invasive Dengue Vectors - John Soghigian; Kathryn Gibbs; Ashleigh Stanton; Rachel Kaiser; Todd Livdahl (SAGE Publishing, 2014)
Two invasive mosquitoes, Aedes aegypti and Aedes albopictus , have been interacting during the course of a rapid range expansion by A. albopictus. We investigated the potential for interspecific feeding interference by male mosquitoes interacting with females within and between these species. A. aegypti feeding on both sugar and blood was suppressed when females of this species were exposed to A. albopictus males, but no change was observed when exposed to conspecifics. A. albopictus feeding was not affected by males of either species. The potential consequences of these behaviors are discussed within the context of other known interspecific effects, all of which appear to favor the displacement of A. aegypti by A. albopictus .